Stability of Pickering Emulsions with Different Types of Emulsifiers at Different pH Values - Li, Jiachen (International Journal of Agriculture and Food Sciences Research, 2025)
Pickering emulsions stabilized by solid particles have potential applications in foods, personal care, and drug delivery. Particle wettability and charge, which depend on pH, are key factors influencing emulsion stability. This scoping review summarizes recent research on the effects of pH on stability of common Pickering emulsifiers. Studies on inorganic particles, polymers, and biopolymers published from 2013-2023 were included. Results indicate pH relative to the emulsifier's isoelectric point impacts stability. Silica nanoparticles showed optimal stability around pH 5 due to increased hydrophobicity and flocculation. Protein-based particles like hordein were more stable at acidic pHs below their isoelectric point. In contrast, nanocellulose Pickering emulsions demonstrated remarkable stability across pH 1-13, attributed to strong van der Waals and hydrogen bonding interactions. Overall, adjusting pH can modify emulsifier surface chemistry to improve Pickering emulsion stability, with exact effects depending on the emulsifier system. Further research directly comparing different particles under standardized conditions is needed. This review summarizes current knowledge on pH effects on emulsion stability for key food-relevant Pickering emulsifiers. The insights could help guide selection of appropriate pH conditions when formulating stable Pickering emulsions.